2012
DOI: 10.1002/imhj.21324
|View full text |Cite
|
Sign up to set email alerts
|

War trauma lingers on: Associations between maternal posttraumatic stress disorder, parent–child interaction, and child development

Abstract: Maternal traumatization has been proposed as a risk factor for child development, but the mechanisms involved are poorly understood. This study analyzed the interrelations among maternal posttraumatic stress symptoms, parent-child interaction (emotional availability), and infants' psychosocial functioning and development among 49 asylum-seeker and refugee mothers and their children (18-42 months). Measures included assessment of mothers' trauma and comorbid symptoms (Harvard Trauma Questionnaire: R.F. Mollica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
135
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(145 citation statements)
references
References 47 publications
6
135
4
Order By: Relevance
“…Parents in our study seemed to experience slightly more feelings of shame and fewer feelings of distress related to the sexual abuse of their child compared to parents whose children completed trauma-focused cognitive behavioural therapy for different forms of trauma (Holt, Cohen, & Mannarino, 2015). In earlier studies, parental PTSD symptoms and psychopathology were found to be related to child PTSD symptoms, (sexual) behaviour problems, and lower parent–child relationship quality (Elkovitch, Latzman, Hansen, & Flood, 2009; Levendosky & Graham-Bermann, 2000; van Ee, Kleber, & Mooren, 2012). We found similar associations, except for sexual behaviour problems.…”
Section: Discussionmentioning
confidence: 98%
“…Parents in our study seemed to experience slightly more feelings of shame and fewer feelings of distress related to the sexual abuse of their child compared to parents whose children completed trauma-focused cognitive behavioural therapy for different forms of trauma (Holt, Cohen, & Mannarino, 2015). In earlier studies, parental PTSD symptoms and psychopathology were found to be related to child PTSD symptoms, (sexual) behaviour problems, and lower parent–child relationship quality (Elkovitch, Latzman, Hansen, & Flood, 2009; Levendosky & Graham-Bermann, 2000; van Ee, Kleber, & Mooren, 2012). We found similar associations, except for sexual behaviour problems.…”
Section: Discussionmentioning
confidence: 98%
“…Children's emotions may be a reminder of their own trauma which may trigger avoidance (Lieberman, 2004). A study of mother-child dyads in which mothers were traumatized by war, but children were not exposed to war, showed that maternal posttraumatic stress symptoms were negatively associated with parent-child relation quality, and children showed lower levels of responsiveness and involvement in mother-child interactions (van Ee, Kleber, & Mooren, 2012).…”
Section: Parent-child Emotion Dialogues and Exposure To Ipvmentioning
confidence: 99%
“…Children's emotions may be a reminder of their own trauma which may trigger avoidance (Lieberman, 2004). A study of mother-child dyads in which mothers were traumatized by war, but children were not exposed to war, showed that maternal posttraumatic stress symptoms were negatively associated with parent-child relation quality, and children showed lower levels of responsiveness and involvement in mother-child interactions (van Ee, Kleber, & Mooren, 2012).In addition to the high risk of maternal posttraumatic stress in IPV-exposed families, research also shows that parents in these families often have been exposed to adverse childhood experiences (ACEs) themselves (Bensley, Van Eenwyk, & Simmons, 2003). Parents exposed to ACEs are at increased risk to develop psychopathology (Anda et al, 2006), and parental…”
mentioning
confidence: 99%
“…Intergenerational trauma associated with decades or centuries of oppression and wars can upset child care and parentÀchild attachment (e.g., Van Ee, Kleber, & Mooren, 2012). Severe or repeated adverse experiences in vital periods of development can seriously affect emotional and physiological regulation and interpersonal relating, and lead to increased vulnerability to later stressors (e.g., Fonagy & Target, 2005;Hinton & Kirmayer, 2013;Schore, 2002).…”
mentioning
confidence: 99%